Comparison of Melatonin Levels in the Colostrum between Vaginal Delivery and Cesarean Delivery - Namlı Kalem, Müberra; Kalem, Ziya; Yuce, Tuncay; Bakırarar, Batuhan; Söylemez, Feride (American Journal of Perinatology, 2018)
Objective This study aims to compare melatonin levels in colostrum between vaginal and cesarean delivery.Study Design This cross-sectional study was conducted with 139 mothers who gave live births between February 2016 and December 2016. The mothers were divided into three groups according to the mode of delivery: 60 mothers (43.2%) in the vaginal delivery group, 47 mothers (33.8%) in the elective cesarean delivery, and 32 mothers (23.0%) in the emergency cesarean delivery group. Colostrum of the mothers was taken between 01:00 and 03:00 a.m. within 48 to 72 hours following the delivery, and the melatonin levels were measured using the enzyme-linked immunosorbent assay (ELISA) and compared between the groups.Results The melatonin levels in the colostrum were the highest in the vaginal delivery group, lower in the elective cesarean section group, and the lowest in the emergency cesarean group (265.7 ± 74.3, 204.9 ± 55.6, and 167.1 ± 48.1, respectively; p < 0.001). The melatonin levels in the colostrum did not differ according to the demographic characteristics of the mothers, gestational age, birth weight, newborn sex, the Appearance, Pulse, Grimace, Activity, and Respiration (APGAR) scores, and for the requirement for neonatal intensive care.Conclusion Our study results showed that melatonin levels in the colostrum of the mothers who delivered vaginally were higher than those who delivered by cesarean section. Considering the known benefits of melatonin for the newborns, we believe that vaginal delivery poses an advantage.
Keywords: melatonin; colostrum; breast-milk; vaginal delivery; cesarean section